1991
DOI: 10.1136/bmj.303.6800.435
|View full text |Cite
|
Sign up to set email alerts
|

Fatal myocardial infarction in the Scottish adjuvant tamoxifen trial. The Scottish Breast Cancer Committee.

Abstract: Objective-To investigate the incidence of fatal myocardial infarction in women in the two randomised arms of the Scottish adjuvant tamoxifen trial.Design-Retrospective review of hospital notes to determine with the greatest possible certainty women who had died of an acute myocardial infarction.Setting-Scottish Cancer Trials Office, the University of Edinburgh.Patients-1070 postmenopausal women with operable breast cancer who were randomised to receive either adjuvant tamoxifen for five years or until relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(107 citation statements)
references
References 18 publications
3
102
0
2
Order By: Relevance
“…A haemodilutory action may contribute to the cardioprotective effects of tamoxifen in postmenopausal women. Studies in women with breast cancer suggest that tamoxifen may substantially reduce the risk of dying from cardiovascular disease [1,6,7]. This effect is likely to be, in part, attributable to favourable effects on serum lipids and haemostatic factors [3,5,13].…”
Section: Discussionmentioning
confidence: 99%
“…A haemodilutory action may contribute to the cardioprotective effects of tamoxifen in postmenopausal women. Studies in women with breast cancer suggest that tamoxifen may substantially reduce the risk of dying from cardiovascular disease [1,6,7]. This effect is likely to be, in part, attributable to favourable effects on serum lipids and haemostatic factors [3,5,13].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of response bore a greater similarity to Tamoxifen (the anti-oestrogen drug successfully employed in breast-cancer treatment) than to HRT. This overall similarity between Raloxifene and Tamoxifen may be important, since the changes in risk factors induced by Tamoxifen may be responsible for the observed decrease in CHD mortality in women receiving Tamoxifen (McDonald & Stewart, 1991).…”
Section: Hormone-replacement Therapymentioning
confidence: 89%
“…The effects of tamoxifen therapy on HDL cholesterol have varied across previous studies and have mostly been marginal. Retrospective studies have suggested a reduction of cardiac morbidity among tamoxifen users (McDonald and Stewart, 1991;Rutqvist and Mattsson, 1993), which has been related to the cholesterol-lowering effect of antioestrogens. However, a large double-blind, randomised, placebo-controlled NSABP Breast Cancer Prevention Trial (BCPT) reported that prophylactic tamoxifen did not influence cardiovascular risk in 13 388 women (Fisher et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Uniformly, the levels of total cholesterol and LDL cholesterol decrease significantly during tamoxifen treatment, but the effects on HDL cholesterol and triglycerides have varied (Love et al, 1990;Grey et al, 1995;Saarto et al, 1996b;Decensi et al, 1998). Two retrospective, randomised trials suggested that tamoxifen might have a cardioprotective effect in postmenopausal women (McDonald and Stewart, 1991;Rutqvist and Mattsson, 1993). However, a large placebo-controlled randomised study failed to show any effects of tamoxifen on cardiovascular risk (Fisher et al, 1998).…”
mentioning
confidence: 99%